Relationship Between Labor and Delivery Unit Management Practices and Maternal Outcomes. Issue 1 (March 2018) - Plough, A.C.; Galvin, G.; Li, Z.; Lipsitz, S.R.; Alidina, S.; Henrich, N.J.; Hirschhorn, L.R.; Berry, W.R.; Gawande, A.A.; Peter, D.; McDonald, R.; Caldwell, D.L.; et al.
Abstract : ( Obstet Gynecol . 2017;130(2):358–365) The specific management practices of labor and delivery units and their sensitivity to operational pressures have not been well assessed in the context of improved patient outcomes. In the present review, the authors assessed whether or not labor and delivery unit management practices that proactively mitigated unit challenges were independently associated with lower risk of primary cesarean delivery, prolonged length of stay, and adverse maternal outcomes in low-risk patients.